Combined assessment of EGFR-related molecules to predict outcome of 1st-line cetuximab-containing chemotherapy for metastatic colorectal cancer. Issue 7 (2nd July 2016) - Sunakawa, Yu; Yang, Dongyun; Moran, Miriana; Astrow, Stephanie H.; Tsuji, Akihito; Stephens, Craig; Zhang, Wu; Cao, Shu; Takahashi, Takehiro; Denda, Tadamichi; Shimada, Ken; Kochi, Mitsugu; et al.
ABSTRACT: Several studies have reported that epidermal growth factor receptor (EGFR)-related molecules may serve as predictors of cetuximab treatment for metastatic colorectal cancer (mCRC), such as EGFR gene copy number (GCN), expression of 2 ligands of EGFR, amphiregulin (AREG) and epiregulin (EREG), and EGFR CA simple sequence repeat 1 (CA-SSR1) polymorphism; however, these biomarkers still remain not useful in clinical practice since they have been evaluated using cohorts with patients treated in various settings of chemotherapy. We therefore analyzed associations of mRNA expression of AREG and EREG, EGFR GCN, and CA-SSR1 polymorphism [short (S;≤ 19) / long (L; ≥ 20)] with clinical outcomes in 77 Japanese patients with KRAS exon 2 wild-type mCRC enrolled in phase II trials of FOLFOX ( n = 28/57, UMIN000004197) or SOX ( n = 49/67, UMIN000007022) plus cetuximab as first-line therapy. High AREG expression correlated with significantly better progression-free survival (median 11.6 vs. 66 months, HR 0.52, P = 0.037); moreover, it remained statistically significant in multivariate analysis (HR: 0.48, P = 0.027). S/S genotype of CA-SSR1 predicted severe skin toxicity ( P = 0.040). Patients with both AREG -low and EGFR low-GCN had significantly shorter overall survival than the others (median 22.2 vs. 42.8 months, HR 2.34, P = 0.042). The multivariate analysis showed that molecular status with both AREG -low and EGFR low-GCN was a predictor of worse survival ( P = 0.006). In conclusion, AREG mRNA expression and EGFR CA-SSR1 polymorphism predict survival and skin toxicity, respectively, of initial chemotherapy with cetuximab. Our results also suggest potential prognostic value of the combined assessment of AREG and EGFR GCN for first-line cetuximab treatment.